Odpowiedź :
[tex]a)\\\\-9-x=-21-(-15)\\-9-x=-21+15\\-9-x=-6 /+9\\-x=3 /*(-1)\\x=-3\\\\\text{Od liczby -9 nalezy odjac liczbe -3 (dodac 3)}[/tex]
[tex]b) \\\\-30+x=13-33\\-30+x=-20 /+30\\x=10\\\\\text{Do liczby -30 nalezy dodac 10}[/tex]
Odpowiedź:
-9 - x = -21 - (-15)
-9 -x= -21 +15
-9-x= -6
-x = -6 +9
-x= 3 /*(-1)
x= - 3
Należy odjąć liczbę -3
spr... -9 - (-3) = - 21 - (-15)
-9 + 3 = -21 +15
-6= - 6
L=P
b) -30 +x = 13 -33
-30 +x= -20
x= -20 +30
x= 10
Należy dodać liczbę 10.
spr... -30 + 10= 13 -33
-20= -20
L=P
Szczegółowe wyjaśnienie: